Study of Pre-Monsoon Thunderstorms and Associated Thermodynamic Features Over Bangladesh Using WRF-ARW Model (Dhaka University Journal of Science, 2019)
Thunderstorm is a mesoscale system (from a km to below thousands of km and sustaining less than one hour). Two pre-monsoon thunderstorms events are analyzed in this study which are named as event-1 (0030-0150 UTC of 19 April 2018 over Chattogram) and event-2 (0600-1000 UTC of 4 May 2018 over Dhaka). To predict these events Mean Convective Available Potential Energy (mCAPE), Mean Convective Inhibition Energy (mCINE), K Index (KI), Total totals Index (TTI), wind distribution, and relative humidity (RH) are investigated.The model simulated mCAPE and mCINE values, 18 hours before the events, are found greater than 1700 J/Kg and less than 100 J/Kg respectively which satisfies the conditions for thunderstorms to occur.The KI values are close to 400C and TTI values are greater or equal to 450C for both events. The wind patterns and the high value of mid –tropospheric RH also favors the formation of severe thunderstorm.Dhaka Univ. J. Sci. 67(2): 151-156, 2019 (July)